2019
DOI: 10.1007/s11274-019-2601-5
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated isothermal amplification-lateral-flow dipstick (LAMP-LFD) to detect Mycoplasma ovipneumoniae

Abstract: In order to establish a rapid detection method for Mycoplasma ovipneumoniae , this study used the loop-mediated isothermal amplification (LAMP) technique to carry out nucleic acid amplification and chromatographic visualization via a lateral flow dipstick (LFD) assay. The M. ovipneumoniae elongation factor TU gene ( EF-TU ) was detected using a set of specific primers designed for the EF-TU gene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 38 publications
(37 reference statements)
1
43
0
1
Order By: Relevance
“…Previous studies had demonstrated the efficacy of the PCR and LAMP to detect 16S rRNA and other conserved regions of genomic DNA of M. ovipneumoniae in different clinical specimens, including the nasal swabs and lung samples [4,9,14,15]. In this study, the RPA primers and probes were also designed based on the 16S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies had demonstrated the efficacy of the PCR and LAMP to detect 16S rRNA and other conserved regions of genomic DNA of M. ovipneumoniae in different clinical specimens, including the nasal swabs and lung samples [4,9,14,15]. In this study, the RPA primers and probes were also designed based on the 16S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…Since first confirmed in Australia in 1972, infections by M. ovipneumoniae have been an endemic problem worldwide and have caused severe economic losses to the sheep and goat industry [10][11][12]. Bacteriological culture of M. ovipneumoniae is currently the gold standard for diagnosis, however, the culture is cumbersome and time-consuming due to the fastidious nature of the bacterium as well as that the follows required species identification by biochemical or serological tests, which make the assay burdensome for the routine applications [13][14][15]. In addition, the bacterial isolation may be hampered by sample contamination and prior antibiotic treatments received by the diseased animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriological culture of M. ovipneumoniae is currently the gold standard for diagnosis, however, the culture is cumbersome and time-consuming due to the fastidious nature of the bacterium as well as that the follows required species identification by biochemical, serological or molecular tests, which make the assay burdensome for the routine applications [13][14][15]. In addition, the bacterial isolation may be hampered by sample contamination and prior antibiotic treatments received by the diseased animals.…”
Section: Ovipneumoniaementioning
confidence: 99%
“…However, seroconversion to M. ovipneumoniae is often delayed after natural infection, which makes the serology less effective in detecting early-stages of infection in herds, and unsuitable for detecting acute mycoplasmal pneumonia in the field [9,14]. Different nucleic acid amplification-based methods have been described to be sensitive and specific for M. ovipneumoniae, i.e.…”
Section: Ovipneumoniaementioning
confidence: 99%